Risk factors for oral cancer in newly diagnosed patients aged 45 years and younger: a case-control study in Southern England - Llewellyn, C. D.; Johnson, N. W.; Warnakulasuriya, K. A. A. S. (Journal of oral pathology & medicine, 2004)
Background:  This case–control study aimed to identify the risk factors for oral cancer in patients aged 45 years and under. Methods:  Patients were recruited over a 3‐year period between 1999 and 2001 from 14 hospitals in the southeast of England, UK. Results:  Fifty‐three (80%) newly diagnosed patients with squamous cell carcinoma (SCC) of the oral cavity participated. The mean age of cases at diagnosis was 38.5 years (SD = 7.0) and 53% were male. Patients were interviewed about main risk factors of tobacco, alcohol, cannabis and their consumption of fresh fruit and vegetables in the past. Ninety‐one matched control patients were also recruited. Odds ratios (ORs) and 95% confidence intervals (CI) were obtained from adjusted conditional logistic analyses. Significantly elevated ORs were evidenced amongst males who had started to smoke under the age of 16 years (OR = 14.3; 95% CI: 1.1–178.8). A significant reduction in risk was also shown for ex‐smokers (OR = 0.2; 95% CI: 0.5–0.8). Consumption of alcohol in excess of recommended amounts also produced an eightfold risk in males (OR = 8.1; 95% CI: 1.6–40.1) and over a fourfold risk of oral cancer from the consumption of excessive amounts of alcohol and having ever smoked (OR = 4.4; 95% CI: 1.1–17.7). Conclusion:  The study shows that the traditional behavioural risk factors are present in younger people diagnosed with oral cancer. The relatively short duration of exposure and the substantial number of cases without any known risk factors, particularly amongst females, however, suggest that factors other than tobacco and alcohol may also be implicated in the development of oral cancer in a proportion of these younger patients.